The Tradition Of The Shalat Qadha Umur In Bedaro - Sulhani Sulhani*; Masburiyah Masburiyah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to find the factors that cause the Bedaro community to carry out the Shalat Qadha umur and examine and study the position of Shalat Qadha umur in terms of Islamic law. This type of research is qualitative descriptive field research using a Sociological Normative approach. The research location was in the village of Bedaro, Muko-Muko Bathin VII Tanjung Agung District, Jambi Province. The research data was obtained by observation, interview and documentation methods as well as material contained in books, journals and other literature which are still related to the problems studied. The results of the research obtained are the factors of the Bedaro community carrying out the Shalat Qadha Umur. First, the Shalat qadha at the age is carried out with the intention of replacing the prayer that has been abandoned, secondly, to get multiple rewards, thirdly, to increase friendship and fourthly, the event to increase worship to Allah SWT, such as alms and infaq and Fifth, as a venue for da'wah and the implementation of the Shalat Qadha does not conflict with Islam, the implementation of the Shalat qadha umur is solely to fill activities in the month of Ramadan only, then it is also an effort to revive or continue religious traditions that have existed for a long time.